Theorizing Rhetorical-Affective Workflows: Behind the Scenes with Webtext Authors. - Shivener, Rich (College English, 2020)
An introduction is presented in which the editor discusses articles in the issue on topics including Scholarly Editing, unseen and affective work, and inclusion activism.